(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
SARS-CoV-2, or COVID-19, is a quickly spreading global virus that has been reported as a pandemic by the World Health Organisation (WHO). COVID-19 is spread by droplets or direct contact and, in most cases, infects the respiratory tract leading to pneumonia and, in around 15% of cases, to acute respiratory distress syndrome (ARDS). Mortality in COVID-19 patients has also been linked to the existence of the virus-induced cytokine storm. Excessive pro-inflammatory cytokine production contributes to the aggravation of ARDS and significant damage to tissues, leading to multi-organ failure and death. The cytokine storm’s pathogenesis is very complex. Much data suggests that the extreme worsening in several patients was directly linked to the cytokine storm in their bodies during the COVID-19 epidemic. This article discusses the cause of incidence and management methods of the inflammatory storm caused by the COVID-19 virus to offer useful clinical treatment advice without using drugs.